Biofilm inhibition and mode of action of epigallocatechin gallate against Vibrio mimicus. (July 2020) - Li, Rui; Lu, Jieyuan; Duan, Hebo; Yang, Jun; Tang, Changbo
Abstract: Vibrio mimicus is a relatively rare food-borne pathogen in seafood and water. Rare reports have been published to investigate the biofilm of Vibrio mimicus . (−)-epigallocatechin-3-gallate (EGCG), the major polyphenolic component of tea, can interfere with bacterial biofilm formation. This study showed that Vibrio mimicus was capable of forming high amounts of biofilms in various culture media. Sub-MICs of EGCG significantly reduced the biofilm production of Vibrio mimicus at 15 °C, 28 °C and 37 °C. Confocal laser-scanning microscope (CLSM) observation proved that the architecture of Vibrio mimicus biofilm was affected by EGCG at the concentration of 64 μg/mL (1/4 MIC). EGCG reduced Vibrio mimicus autoaggregation and swimming motility. EGCG also increased membrane permeability and ROS production, caused cell membrane damage and led to potassium leakage. These may contribute to the antibiofilm efficacy of EGCG against Vibrio mimicus . Our work showed the inhibitory effects of sub-MICs of EGCG on Vibrio mimicus biofilm for the first time, supporting the potential application of EGCG as a natural antibiofilm agent in the food industry. Highlights: Sub-MICs of EGCG inhibited Vibiro mimicus biofilm. EGCG reduced autoaggregation and swimming motility. EGCG increased ROS and membrane permeability. EGCG induced membrane damage and potassium leakage.